2019
DOI: 10.13106/jafeb.2019.vol6.no4.139
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Linkages between Food Inflation and Its Volatility: Evidence from Sri Lankan Economy

Abstract: This study examines the dynamic linkages between food price inflation and its volatility in the context of Sri Lanka. The empirical evidence derived from the monthly data for the period from 2003M1 to 2017M12 for Sri Lanka. The relationship between inflation rate and inflation volatility has attracted more attention by theoretical and empirical macroeconomists. Empirical studies on the relationship between food inflation and food inflation variability is scarce in the literature. Food price inflation is define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, the empirical results had two models: linear and nonlinear relationships (Al-Khulaifi, 2018;Mustafa, & Sivarajasingham, 2019). Keynes's research indicated that, in the short term, there would be a trade-off between the inflation and growth, i.e., a high inflation rate made GDP growth and during this period, growth and inflation rate were positively correlated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the empirical results had two models: linear and nonlinear relationships (Al-Khulaifi, 2018;Mustafa, & Sivarajasingham, 2019). Keynes's research indicated that, in the short term, there would be a trade-off between the inflation and growth, i.e., a high inflation rate made GDP growth and during this period, growth and inflation rate were positively correlated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the authors' results were a negative inflation-growth relationship that was found to exist in the economy of Pakistan (Muhammad, Imran, & Fatima, 2011). There are some research topics on inflation and economic growth that showed that inflation impacts on each countries' different economic growth, which belongs to each countries' monetary policy (Mustafa & Sivarajasingham, 2019;Wulandari, Utomo, Narmaditya, & Kamaludin, 2019;Bong & Premaratne, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Food commodities, particularly rice, are increasingly expensive and are predicted to lead to fluctuations that can be risky for consumers, producers, and the government (Mustafa & Sivarajasingham, 2019). The fluctuations from the calculation of a price that does not reflect a market performance will lead to mistakes in policymaking by the government as the regulator.…”
Section: Introductionmentioning
confidence: 99%